Manajemen Risiko Penyaluran Dana Zakat pada Badan Amil Zakat Nasional (BAZNAS) Kabupaten Pasaman Barat - Hamima, Nur; Kasmuri, Kasmuri; Indah Sari, Chitra; Asrida, Asrida (ZAWA: Management of Zakat and Waqf Journal, 2025)
This research is motivated by the importance of risk management for BAZNAS West Pasaman Regency which must be implemented in order to achieve the goals of BAZNAS to determine the risk management of the distribution of zakat funds is appropriate andk reaches the target or not. This type of research is field research with a qualitative approach. The data source is primary data with interview and documentation collection techniques. The result of the research is that the risk management applied by BAZNAS still adheres to the holy Qur’an leeter At-Taubah verse (60), the ap[licable zakat law, the BAZNAS program and SOP, always evaluates and is audited by an externalpublic accountant. Basically, the commonly known risk are pure risk and speculative risk, here the distribution of zakat funds is categorized as pure risk because if the distribution of zakat funds is not on target, the risk that is likely to occur is that the mustahik who receives zakat is not right. Risks that are classified according to levels in the form of moderate risk of a decrease between raising muzakki and beneficiaries and the realization of mustahik/beneficiaries based on programs (people), health, low risk with word of diatribe, lack of gratitude both to BAZNAS and to the distribution of zakat funds, moderate risk with delays in the distribution of zakat funds at BAZNAS West Pasaman Regency.